Label Free Detection of Adenosine Based on Hemin/G-Quadruplex Peroxidase-Mimicking DNAzyme as Bioelectrocatalyst - Li1, Yu; Li1, Sen; Xia2, Ge-Qing; Wang1, Yuansheng (Asian Journal of Chemistry, 2013)
The hemin/G-quadruplex horseradish peroxidase-mimicking DNAzyme is assembled on gold electrodes. It reveals bioelectrocatalytic properties and electrocatalyzes the reduction of H2O2. The bioelectrocatalytic functions of the hemin/G-quadruplex DNAzyme is used to develop electrochemical sensor for the detection of adenosine. Hairpin nucleic structure that includes the G-quadruplex sequence in a caged configuration and the nucleic acid sequence complementary to the aptamer sequence for adenosine, is immobilized on gold-electrode surfaces. In the presence of the analyte, the hairpin structure is opened and the hemin/G-quadruplex horseradish peroxidase-mimicking DNAzyme structure is generated on the electrode surfaces. The bioelectrocatalytic cathodic current generated by the functionalized electrode, upon the electrochemical reduction of H2O2, provides a way for the detection of adenosine.